Pelaksanaan tata cara penunjukan wali di Kecamatan Gunung Tuleh Kabupaten Pasaman Barat - Aulia, Mita; Nasution, Muhammad Arsad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
A guardian is a person or entity that in fact exercises parental power over a child. Along with the implementation of Government Regulation Number 29 of 2019 concerning Terms and Procedures for Appointment of Child Guardianship in Review of Islamic Law (Case Study In Gunung Tuleh District, West Pasaman Regency). The purpose of this research is how to implement Government Regulation Number 29 of 2019 concerning Terms and Procedures for Appointing Child Guardianship in Gunung Tuleh District, Pasaman Barat Regency, how is the view of Islamic Law regarding the Implementation of Government Regulation Number 29 of 2019 concerning Terms and Procedures for Appointing Child Guardianship in the Subdistrict Mount Tuleh, West Pasaman Regency. This type of research used in this research is field research, namely collecting data from jorong, pious ulama, notes, adoptive parents who have conducted child research in Gunung Tuleh District, West Pasaman Regency. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that the reason for the guardianship of the child by the adoptive parents is because they do not have children, the biological parents have a poor economy and have compassion for the biological parents. The implementation of child guardianship is only limited to a letter of agreement, it is not recorded at the population service and there is no stipulation. Then in terms of population administration, especially birth certificates and family cards (KK) for all respondents, the adopted children are named after their adoptive parents. And change the status of the child to become a biological child. So the implementation of child guardianship in Islamic law is not in accordance with Islamic law. And from this it can be seen that from the implementation of child guardianship, not from the appointment of a guardian based on the request or will of the parents. And change the status of adopted children to biological children.